Estimating the Natural Rates in a Simple New Keynesian Framework - Hilde C. Bjørnland; Kai Leitemo; Junior Maih (Norges Bank, 2007)
The time-varying natural rate of interest and output and the implied medium term inflation target for the US economy are estimated over the period 1983-2005. The estimation is conducted within the New-Keynesian framework using Bayesian and Kalman-filter estimation techniques. With the model-consistent estimate of the output gap, we get a small weight on the backward-looking component of the New-Keynesian Phillips curve - similar to what is obtained in studies which use labor share of income as a driver for inflation (e.g., Galièt al., 2001, 2003). The turning points of the business cycle are nevertheless broadly consistent with those of CBO/NBER. We find considerable variation in the natural rate of interest while the inflation target has been close to 2% over the last decade.
hdl:11250/2498264
Keywords: C51; E32; E37; E52; 330; New-Keynesian model; natural rate of interest; natural rate of output; inflation target